Osmotic Treatment of Orange and Pink Sweet Potato-Mass Transfer Rate and Efficiency - Lončar, Biljana; Filipović, Vladimir; Šovljanski, Olja; Pezo, Lato; Knežević, Violeta; Šuput, Danijela; Aćimović, Milica (Analecta Technica Szegedinensia, 2024)
Sweet potatoes (Ipomoea batatas) are globally cultivated due to its adaptability, high nutritional value, and short growing season, tolerance to high-temperature soils, low fertility, and minimal pest or disease issues, making it a valuable asset to the food industry. Osmotic treatment, a renowned preservation technique requiring mild temperatures and minimal energy, has gained prominence. Over ten years of research at the Faculty of Technology Novi Sad has pioneered the use of sugar beet molasses as an effective osmotic solution for drying different herbs, fruits, vegetables, and meat. This study specifically focused on osmotically treating samples of pink and orange sweet potatoes in sugar beet molasses (80% w/w) to explore the influence of solution temperatures (20°C, 35°C, and 50°C) and osmotic treatment durations (1h, 3h, and 5h) on mass transfer rate and treatment efficiency. The Principal Component Analysis (PCA) and color correlation analysis were employed to illustrate the connections between different sweet potato samples. Findings indicate that the mass transfer rate peaks at the onset of the process. Particularly with the highest temperature after 1h of osmotic treatment The highest values for RWL and RSG (13.33±0.02, 1.85±0.04 and 11.51±0.02, accordingly) were obtained for both orange ((15.19±0.08 g/(gi.s.w.·s)·105and 4.53±0.06 g/(gi.s.w.·s)·105) and pink sweet potato ((9.91±0.02 g/(gi.s.w.·s)·105 and 3.78±0.04 g/(gi.s.w.·s)·105), respectively. Notably, diffusion is most rapid within the initial three hours, suggesting potential reductions in processing time aligned with these results.